2021
DOI: 10.1159/000514808
|View full text |Cite
|
Sign up to set email alerts
|

External Validity of Somatostatin Analogs Trials in Advanced Neuroendocrine Neoplasms: The GETNE-TRASGU Study

Abstract: Introduction: Somatostatin analogues (SSA) prolong progression-free survival (PFS) in patients with well-differentiated gastroenteropancreatic neuroendocrine tumors (GEP-NETs). However, the eligibility criteria in randomized clinical trials (RCTs) have been restricted, which contrasts with the vast heterogeneity found in NETs. Methods: We identified patients with well-differentiated (Ki67% ≤20%), metastatic GEP-NETs treated in first-line with SSA monotherapy from the Spanish R-GETNE registry. The therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…GETNE-TRASGU study recruited 535 metastatic, well-differentiated GEP-NETs patients using SSAs monotherapy as the first-line treatment. [15,16] The results showed that the mPFS was 28.7months (95% CI, 23.8–31.1) and the median overall survival (mOS) was 85.9months (95% CI, 71.5–96.7). Meanwhile, predictive factors of SSA as first-line therapy in advanced GEP-NETs were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…GETNE-TRASGU study recruited 535 metastatic, well-differentiated GEP-NETs patients using SSAs monotherapy as the first-line treatment. [15,16] The results showed that the mPFS was 28.7months (95% CI, 23.8–31.1) and the median overall survival (mOS) was 85.9months (95% CI, 71.5–96.7). Meanwhile, predictive factors of SSA as first-line therapy in advanced GEP-NETs were investigated.…”
Section: Methodsmentioning
confidence: 99%
“… 5 , 7 , 8 Reliable comparative data on the efficacy of LAN and OCT are lacking, a Spanish R-GETNE registry study ( n = 535) showed similar effects of LAN-AG and OCT–LAR on PFS [hazard ratio (HR) of 0.9 for LAN versus OCT, 95% confidence interval (CI): 0.71–1.12]. 81 Furthermore, although not systematically studied, there are anecdotal reports that switching between SSA compounds may result in varying degrees of response. 51 , 82 Pharmacologically, OCT and LAN have a similar affinity for SSTR2 (IC 50 0.4 versus 0.75 nmol/L) and SSTR5 (IC 50 5.6 versus 5.2 nmol/L), but their long-acting formulations have different pharmacokinetic profiles (OCT–LAR: prolonged plateau phase for about 30 days after an initial increase and a lag phase; LAN-AG: peak concentration on day 1 and then elimination with a half-life of 25.5 days).…”
Section: Ssa Monotherapy In Netmentioning
confidence: 99%
“… 84 Apart from lower rates of treatment discontinuation due to AEs with LAN-AG (3% versus 12% in the respective phase III studies), the safety profile is generally comparable. 55 , 68 , 81 , 84 Detailed analyses of the pivotal studies are presented in the following section.…”
Section: Ssa Monotherapy In Netmentioning
confidence: 99%
“…Long-acting SST analogues (Octreotide, 20mg/m or Lanreotide, 90mg/28 d, 12months, im) decreased blood transfusion in patients with refractory bleeding from gastrointestinal angiodysplasias (90). SST prolongs progression-free survival (PFS) in individual precision medicine; global multicenter studies have confirmed high dose-SST (Octreotide, 30mg/4ws) (Lanreotide, 120mg/4ws) is an active and safe option in patients with progressive well-differentiated gastroenteropancreatic NETs, and an independent individualized prediction model could be a valuable tool for making treatment decisions in clinical practice for SST-treated patients (91)(92)(93). Therefore, powerful prediction tools, drug-combination, and conjugated-medicine are important to limit the side effects of SST analogues in fatigue, diarrhoea, constipation, abdominal pain, nausea, cholelithiasis and hyperinsulinism, and necrotizing enterocolitis in infants (72,94,95).…”
Section: Sst-sstrs In Basic Research and Clinical Medicinementioning
confidence: 99%